2000
DOI: 10.1046/j.1365-8711.2000.03577.x
|View full text |Cite
|
Sign up to set email alerts
|

Elemental abundance analyses with DAO spectrograms - XXIII. The superficially normal stars 28 And (A7 III) and 99 Her (F7 V)

Abstract: Elemental abundances of 28 And (A7 III) and 99 Her (F7 V), which have modest rotational velocities, are derived in a manner consistent with previous studies in this series of papers. The values for 28 And, a δ Scuti variable, show that it is slightly metal‐poor, but not a classical Am star. 99 Her, which is somewhat more metal‐poor, has a rather small microturbulence for its spectral type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…We used the abundances of non-variable F-and A-type stars published by Adelman et al (1997Adelman et al ( , 2000, Erspamer & North (2003) and Hill (1995), to generate a typical abundance pattern for stars of similar spectral types. From a direct comparison, we showed that the mean abundance pattern of our sample of δ Scuti stars and of the non-variable F-and A-type stars are comparable.…”
Section: Discussionmentioning
confidence: 99%
“…We used the abundances of non-variable F-and A-type stars published by Adelman et al (1997Adelman et al ( , 2000, Erspamer & North (2003) and Hill (1995), to generate a typical abundance pattern for stars of similar spectral types. From a direct comparison, we showed that the mean abundance pattern of our sample of δ Scuti stars and of the non-variable F-and A-type stars are comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, up to about 10 500 K abundances increase with temperature, which immediately calls for another investigation: is there a similar trend for normal stars and/or is this trend artificially caused by incorrect model atmospheres and spectrum reduction techniques? For this purpose we compiled Cr and Fe abundances for normal, superficially-normal, Am and δ Scuti-type stars with low rotational velocities (v e sin i < 50 km s −1 ) from papers by Varenne & Monier (1999, Hyades A and F stars), Hill & Landstreet (1993), Mittermayer & Weiss (2003), and from numerous papers by Adelman and co-workers: Adelman (1991, 1994, 1996, Adelman & Davis Philip (1992), Adelman et al (1997Adelman et al ( , 2000Adelman et al ( , 2001, , Adelman & Albayrak (1998), Pintado & Adelman (2003), and Kocer et al (2003).…”
Section: Spectroscopic Signature Of Roap Starsmentioning
confidence: 99%
“…The reasoning applied to E s is the same here as it is for example (5). In a procedure that is intermediate between this example and example (5), values of f s + E s and f are compared without subtraction (see, for example, Adelman et al 2000). Examples of this kind of analysis are given by Klochkova & Panchuk (1987, 1990).…”
Section: ) Differential Analysis (Relative To the Sun)mentioning
confidence: 99%